(untitled) (Materiali di Estetica. Terza serie, 2024)
The author presents a synthesis of his presentations at the Collegio Ghislieri in Pavia and the Casa della Cultura in Milan, focusing on the intellectual legacy of Fulvio Papi and his contributions to the journal "Materiali di Estetica." The author highlights Papi’s philosophical dialogue across various disciplines, reflecting on Papi’s approach that transcends traditional scholarly boundaries. He also delves into Papi’s interpretation of existential and religious themes, particularly through the works of Franz Kafka, illustrating Papi’s engagement with the complexities of human existence and the philosophical exploration of justice and truth. The article emphasizes Papi’s role in fostering a multidisciplinary dialogue that continues to influence contemporary philosophical discourse.